An assessment of a portable cyanoacrylate fuming system (LumiFume™) for the development of latent fingermarks. (December 2019) - Jones, Calum; Fraser, Joanna; Deacon, Paul; Lindsay, Maurice; Carlysle-Davies, Felicity; Farrugia, Kevin J.
Highlights: LumiFume™ with Lumicyano™ is an effective crime scene cyanoacrylate fuming system. LumiFume™ with Lumicyano™ was at least as effective as traditional cabinet fuming. As in previous work, the use of BY40 after Lumicyano™ detected additional new marks. A pseudo-operational trial of 300 items demonstrated the effectiveness of LumiFume™. Abstract: The effectiveness and suitability of a portable cyanoacrylate fuming system (LumiFume™) with Lumicyano™ at detecting latent fingermarks was assessed. The first phase of the study compared the LumiFume™ system with traditional cabinet fuming and black/white powder suspension for the development of latent fingermarks on a variety of surfaces (glass, plastic bin bag, laminated wood and tile) by means of depletion series' from 10 donors and four ageing periods (1, 7, 14 and 28 days). The portable fuming system provided superior quality of developed marks on glass and laminated wood whereas powder suspension was better on bin bags and all three techniques were comparable on tile. A decrease in mark quality was recorded from 1 to 14 days for the fuming techniques before an increase at 28 days. Lumicyano™ fluorescence stability studies over a 28 day period by means of depletion series' on glass slides and plastic bin bags revealed better quality marks for the portable system LumiFume™; however, storing marks under light conditions expedited deterioration for both systems. All marks developed with Lumicyano™ were subsequently treated with BY40 resulting in further improvement in mark quality for all substrates and ageing periods, with the exception of laminated wood which absorbed the fluorescent stain reducing the contrast in the process. The second phase of the study consisted of a pseudo-operational trial on 300 various substrates (e.g. glass bottles, aluminium cans, plastic bags) recovered from recycling bins. LumiFume™ and Lumicyano™ yielded 1469 marks whereas Lumicyano™ cabinet fuming and powder suspension yielded 1026 and 641 marks respectively. Similar to the first phase of the study, further treatment of the Lumicyano™ treated marks with BY40 resulted in further quality improvement as well as additional new marks. The LumiFume™ system produced results at least equivalent to the traditional cabinet fuming with Lumicyano™ highlighting its potential for implementation into casework to process crime scenes.